A Feminist Genealogy of the Lived Body? Rethinking the Gendered Body as a Site of Excess and Indeterminacy. Issue 50 (2nd October 2019) - İbrahimhakkıoğlu, Fulden
ABSTRACT: This essay offers a rethinking of the gendered body as both lived and historically constituted. These two dimensions are sometimes seen as irreconcilable, especially by some proponents of post-structuralism who are critical of phenomenology. My contention is that when approaching gender, Merleau-Ponty's paradoxical formulation of the body as "always something other than what it is" can accompany a genealogy of the body. The body, as excessive, indeterminate, and ambiguous in Merleau-Pontian phenomenology, is at the same time the very object and product of certain techniques and procedures developed since the nineteenth century, as Foucault documents. Not only are phenomenology and genealogy compatible in this context, but thinking them together is necessary in order to illuminate the multi-faceted complexity of the embodiment of gender. The weight of this necessity is especially felt when approaching sexual violence, which tends to take place at the very intersection of the body-as-lived and the body-as-constituted.